The Effect of Chlorophyll-a and Sea Surface Temperature on Skipjack Tuna Fishing Areas in FMA 714 - Yudi Ardiansyah Saputra; Muhammad Farhan; Justin Yonathan; Galih Hamdani; Yolando Ambarita; Michael Mahfud Jafar II; Nurani KHOERUNNISA (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Skipjack tuna (Katsuwonus pelamis) is a high economic value pelagic commodity in FMA 714, whose distribution is highly responsive to oceanographic parameters, particularly sea surface temperature and chlorophyll a. This study aims to analyze the influence of sea surface temperature and chlorophyll a distribution on the characteristics of potential skipjack tuna fishing areas in the waters of FMA 714 in 2022. The approach is a quantitative, descriptive method using simple linear regression to correlate NOAA datasets with fish catch statistics. Temporal analysis revealed that oceanographic dynamics are controlled by the monsoon cycle, particularly the upwelling process during the East Season. This period was marked by a drastic decline in sea surface temperature to 28°C in August, in contrast to a sharp surge in chlorophyll a concentration in July-August, reaching 0.48-0.50 mg/m³. Although these water conditions produced dynamic productivity, linear regression analyses showed that sea surface temperature was positively associated with fish catch, while chlorophyll a was negatively associated, though very weakly. Sea surface temperature and chlorophyll a did not have a significant effect on fish catch (p=0.239), indicating that these parameters explained only 23.9% of the variation in catch, with the remaining 76.1% influenced by factors outside the research model. Catch production is largely influenced by fishing gear. Purse seine with a single boat is the most widely used fishing gear, with as many as 2,328 fleets using it. This is another factor in the production of skipjack tuna catches in FMA 714.